Violation of freedom of expression in China. Journalists in the spotlight - Ordóñez, Kruzcaya; Suing, Abel; Cueva, Jorge; Carpio, Lilia (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
This research presents a qualitative analysis of emblematic cases of censorship and violation of freedom of expression of journalists in China. In this nation, journalism has been repressed and censored under the justification of disrespect for the policy based on Xi Jinping’s thinking, which promotes through the law: to fight political corruption and bribery. The aim is to establish an authoritarian policy. Qualitative methodology is applied to identify emerging themes and categories and monitor legal and extralegal restrictions through violations of civic freedoms identified by Freedom House.